2024
DOI: 10.21037/tcr-23-1556
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of a novel web-based nomogram for primary ocular adnexal lymphoma: a real-world analysis based on the Surveillance, Epidemiology, and End Results database

Zhen Chen,
Ling Ye,
Xia Li

Abstract: Background The occurrence rate of primary ocular adnexal lymphoma (POAL) is relatively low, and estimation of prognosis of these patients poses significant challenges. This study aims to investigate the independent prognostic factors of POAL patients and establish a predictive model to provide clinical data for the formulation of standardized treatment plans. Methods We conducted a retrospective analysis by extracting data of POAL patients diagnosed between 2000 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…The most common B-cell lymphoma is EMZL, as previously reported, followed by DLBCL, FL, and MCL [13][14][15][16][17][18]. The results of this study were consistent with those reported in incidence studies of the ocular adnexal region, in which EMZLs are indeed found to be the most frequent lymphoma subtype.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The most common B-cell lymphoma is EMZL, as previously reported, followed by DLBCL, FL, and MCL [13][14][15][16][17][18]. The results of this study were consistent with those reported in incidence studies of the ocular adnexal region, in which EMZLs are indeed found to be the most frequent lymphoma subtype.…”
Section: Discussionsupporting
confidence: 92%
“…The clinical data collected included age at diagnosis, sex, histological subtype, tumor location, rate of survival, outcome, surgical procedure, radiation therapy, chemotherapy, and basic ophthalmological parameters [ 13 ].…”
Section: Methodsmentioning
confidence: 99%